Projeto folhas e o livro didático público de História: um estudo sobre a produção de obras didáticas no Estado do Paraná entre 2003 e 2010 - Thomé , Thaís (2024)
This master's thesis discusses the construction of didactic knowledge produced by teachers from the public education system in Paraná through the Folhas Project and the production of the Public History Textbook (LDP). Both were organized by the Paraná State Department of Education (SEED) between 2003 and 2010. The Folhas Project aimed to provide continuous professional development to teachers in the state education network through a written production, called “Folhas,” which later served as a model for the creation of Public Textbooks distributed by the state. The research explores the construction of the Folhas Project and the Public History Textbook (LDP) through the memories and experiences of the individuals involved, with an emphasis on the production developed by teachers and educational managers. By analyzing the production of school knowledge as a historical process marked by political and cultural disputes, it was understood that the complex relationships between teachers and educational managers influenced the materiality of the Folhas and the LDP, constituting them as a product of this relationship.